2022
DOI: 10.1108/jfrc-01-2022-0003
|View full text |Cite
|
Sign up to set email alerts
|

Institutional quality, macroeconomic uncertainty and efficiency of financial institutions in Sub-Saharan Africa

Abstract: Purpose This paper evaluates how institutions of governance and macroeconomic uncertainty influence efficiency of financial institutions in the subregion of Sub-Saharan Africa (SSA). Data for the empirical inquiry were compiled from relevant sources for 33 countries in the subregion from 2002 to 2019. Empirical estimates verifying hypothesized relationships were carried out using the continuous updating estimator (CUE) by Hansen et al. (1996). Design/methodology/approach The purpose of this paper is to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Meanwhile, studies have shown that best practice in corporate governance requires constant monitoring of external business environment to remain competitive (Dupire & M'Zali, 2018). Relatedly, environmental uncertainty has no significant impact on SAP, suggesting that manufacturing companies in Nigeria do not attach much importance to external information on environmental and social sustainability practice as to constantly monitor the competitive business environment (Abaidoo & Agyapong, 2022). In sum, the insignificant influence of the two external governance factors (i.e., intensity of competition and perceived environmental uncertainty) on SAP (Tables 4 and 5) provides additional evidence that external pressure on companies to implement sustainability initiatives is weak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, studies have shown that best practice in corporate governance requires constant monitoring of external business environment to remain competitive (Dupire & M'Zali, 2018). Relatedly, environmental uncertainty has no significant impact on SAP, suggesting that manufacturing companies in Nigeria do not attach much importance to external information on environmental and social sustainability practice as to constantly monitor the competitive business environment (Abaidoo & Agyapong, 2022). In sum, the insignificant influence of the two external governance factors (i.e., intensity of competition and perceived environmental uncertainty) on SAP (Tables 4 and 5) provides additional evidence that external pressure on companies to implement sustainability initiatives is weak.…”
Section: Discussionmentioning
confidence: 99%
“…Greater level of uncertainty in the environment causes higher importance to be attached to external, non-financial information (Abaidoo & Agyapong, 2022), and this may be associated with high usage of integrated performance measurement system. Conversely, when PEU is low, predictions about the market may be relatively accurate, thus diminishing the need for external and ex-ante information (Gul & Chia, 1994;Naidenova, 2022), and lower usage of SAP.…”
Section: Perceived Environmental Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…The approach adopted in this study differs significantly from that in related studies. For instance, Abaidoo and Agyapong (2022a, b) verified conditions or factors influencing the efficiency of financial institutions, with a specific focus on institutional quality dynamics and macroeconomic uncertainty. However, the approach adopted in this study is significantly different from that of Abaidoo and Agyapong (2022a, b) in terms of the proxies for the key variables examined, model specification procedures and estimation methodology.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Abaidoo and Agyapong (2022a, b) verified conditions or factors influencing the efficiency of financial institutions, with a specific focus on institutional quality dynamics and macroeconomic uncertainty. However, the approach adopted in this study is significantly different from that of Abaidoo and Agyapong (2022a, b) in terms of the proxies for the key variables examined, model specification procedures and estimation methodology. Again, while Abaidoo and Agyapong (2022a, b) focused mainly on the effect of institutional quality, the current study predominantly examines the impact of macroeconomic instability (risk) on the efficiency of financial institutions.…”
Section: Introductionmentioning
confidence: 99%